The effect of endurance- based sports on athlete success and psychological wellbeing - Ozpinar, Saliha; Yucel, Ali Serdar; Korkmaz, Murat; Oztas, Dilek; Kuyucu, Mihalis Michael; Aras, Goksen (Campus Educa Sports Sl, 2025)
The aim of this study is to examine the effects of psychological resilience on sport success and mental health. The relationships between commitment, control and challenge, which are sub-dimensions of psychological resilience, and sport success and psychological wellbeing were evaluated and discussed in detail. Today, the problems arising due to the increasing competitive environment and stress factors have made it more important for athletes to be psychologically strong. Although the relationship between psychological resilience and sport success has been previously examined in the literature, studies evaluating the individual effects of the sub-dimensions of resilience in a large sample group are quite limited. This study aims to overcome this deficiency and make an up-to-date contribution to the subject. A total of 684 students (72 percent male, 28 percent female) studying at the Faculties of Sport Sciences of 16 universities in Istanbul, Ankara, Izmir, Bursa and Antalya participated in the study. Participants completed the Resilience Scale and Mental Health Inventory, and their sporting achievements were evaluated by their coaches using the Sport Achievement Scale. Data were collected via Google Forms (R) and analysed using SPSS 22.0 software with correlation, regression and Granger causality tests. The findings revealed that all resilience sub-dimensions showed positive and significant relationships with sport achievement ( R-2=0.93) and psychological well-being (R-2=0.68). Especially control and challenge factors had the strongest effects. As a result of the research, commitment, control and challenge, which are the sub-dimensions of psychological resilience, significantly affect both success levels and psychological well-being of athletes. Therefore, resilience development programmes for athletes should focus on these areas.
El efecto de los deportes de resistencia en el éxito deportivo y el bienestar psicológico de los atletas
Keywords: sport achievement; mental health; physical strength; endurance; sportive activity